ANALISIS UNSUR INTRINSIK CERPEN MENJAUH UNTUK MENJAGA KARYA NOVITA ANISSA AZZA: PENDEKATAN MIMETIK - Siti Puji Rahayu Ramdani; Hidayanti Hidayanti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
Study this addressed for analyze element intrinsic in short story Avoid for Guard creation Novita women Azza use approach Mimetic . Method my research _ Use in analysis this use method element intrinsic. Source power in study this is short story Avoid for Guard creation Novita women Azza . Technique data collection used in study this is with read in a manner critical and thorough whole content from short story the . Technique data analysis ie discuss or study content short story Avoid for Guard creation Novita women Azza . Results study is could find element intrinsic form, them , angle point of view, plot, setting, character and characterizatio , style language and mandate . Also could find element social in phenomenon that occurs in associated short story to in life world real.